2018
DOI: 10.1111/cei.13110
|View full text |Cite
|
Sign up to set email alerts
|

The induced RNA-binding protein, HuR, targets 3′-UTR region of IL-6 mRNA and enhances its stabilization in periodontitis

Abstract: RNA-binding proteins (RBPs) regulate mRNA stability by binding to the 3'-untranslated region (UTR) region of mRNA. Human antigen-R (HuR), one of the RBPs, is involved in the progression of diseases, such as rheumatoid arthritis, diabetes mellitus and some inflammatory diseases. Interleukin (IL)-6 is a major inflammatory cytokine regulated by HuR binding to mRNA. Periodontal disease (PD) is also an inflammatory disease caused by elevations in IL-6 following an infection by periodontopathogenic bacteria. The inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 48 publications
0
23
0
1
Order By: Relevance
“…Previous study showed that HuR could increase the stability of MMP2 and MMP9 mRNAs [35]. Moreover, some inflammatory cytokines such as CCL-2 and IL-6 are the targets of HuR [36,37]. Thus, HuR may participate in the AAA progression through regulating some different pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study showed that HuR could increase the stability of MMP2 and MMP9 mRNAs [35]. Moreover, some inflammatory cytokines such as CCL-2 and IL-6 are the targets of HuR [36,37]. Thus, HuR may participate in the AAA progression through regulating some different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, the possible mechanisms were still unclear. Previous studies show that HuR regulates the expression of many inflammatory cytokines including IL-6, ICAM-1, CCL-2, IL-17C and TNF-α through binding to their mRNAs [36][37][38][39]. Thus, the increased inflammation caused by Gsα deficiency may be resulted from increased HuR expression.…”
Section: Discussionmentioning
confidence: 99%
“…Stabilization or decay of ARE‐containing mRNAs through interaction with RNA‐binding proteins has been recognized as an important mechanism of posttranscriptional regulation for inflammatory cytokine genes . HuR, a ubiquitously expressed RNA‐binding protein, is linked to the progression of various chronic inflammatory diseases, such as rheumatoid arthritis, diabetes mellitus, and some inflammatory diseases . It has been shown in vitro that HuR binds to and interacts with AREs in mRNAs producing several inflammatory mediators such as cyclooxygenase‐2 (COX‐2), IL‐6, tumor necrosis factor‐alpha (TNF‐α), and chemokine receptor 6 (CCR6) .…”
mentioning
confidence: 99%
“…The 3′UTR is important for the post-transcriptional regulation of genes. Many RBPs, including human antigen R (HuR) [30], tristetraprolin (TTP) [31], and MCPIP1, have been reported to regulate mRNA stability by the 3'UTR.…”
Section: Discussionmentioning
confidence: 99%